2012
DOI: 10.1166/jnn.2012.6770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core–Shell Structure and Chitosan Addition on Catalytic Activities of Copper-Containing Silica–Aluminosilicate Composites in deNOx Reaction by H2

Abstract: Mesoporous silica-aluminosilicate composites were used as supports for selective catalytic reduction of NO by H2 using copper catalyst. Effect of loading techniques and structures of the supports on the catalytic performance were investigated. The nature, the oxidation state of copper, the structural properties and the morphology of the catalysts were characterized by means of UV-vis spectra, Fourier Transform Infrared Spectroscopy (FTIR), nitrogen sorption, and transmission electron microscopy, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…It should be noted that in this work, the Cu loading of the catalysts was increased by using the impregnation method, in which copper predominately exists as CuO species. 5,18 In addition, with higher metal loading, it is more difficult for a copper precursor to infiltrate deeper in the channels of the catalysts and occupy the exchange sites, leading to the formation of more CuO species on the surface of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that in this work, the Cu loading of the catalysts was increased by using the impregnation method, in which copper predominately exists as CuO species. 5,18 In addition, with higher metal loading, it is more difficult for a copper precursor to infiltrate deeper in the channels of the catalysts and occupy the exchange sites, leading to the formation of more CuO species on the surface of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Catalysts. A core−shell structured Al−MCM-41 was synthesized via the method reported by Chamnankid et al (2012), 5 in which cetyl trimethylammonium bromide (CTAB: 98%, APS Ajax Finechem) was used as a structural directing agent whereas tetraethyl orthosilicate (TEOS: 98%, Sigma-Aldrich) and aluminum nitrate (Al-(NO 3 ) 3 •9H 2 O: 98%, QREC) were used as silica and alumina sources, respectively. The molar gel composition was 1SiO 2 :0.2CTAB:100H 2 O, whereas the Al 2 O 3 /SiO 2 ratio was fixed at 0.1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 It was found that the use of Al-MCM-41 as the support also showed a high hydrothermal stability after heating to 800 C in the presence of H 2 O in SCR of NO with C 2 H 4 ; the Al-MCM-41 support is consequently more stabilized than the ZSM-5 support. Based on our previous work, 45 coreshell-structured Al-MCM-41 enhances the performance of NO reduction, and copper can be easily reduced from Cu(II) to Cu(I), which is an active site for de-NO x catalytic reaction. On the other hand, the problem of hydrothermal stability can also be improved by adding Ce as a promoter.…”
Section: Introductionmentioning
confidence: 99%